APPLICATION OF A SOCIO-EMOTIONAL SKILLS PROGRAM IN ADOLESCENTS IN 1ST GRADE OF SECONDARY SCHOOL FOR THE DEVELOPMENT OF THEIR EMOTIONAL INTELLIGENCE - García, Celina Márquez (Journal of Posthumanism, 2025)
This study examined the impact of a social-emotional skills program on adolescents in the first grade of secondary school, with the objective of developing their emotional intelligence. The BarOn Emotional Quotient Inventory (EQ-I) was administered at the outset and conclusion of the intervention, employing a quasi-experimental design with a sample of 46 students. The findings revealed a significant enhancement in overall emotional intelligence, accompanied by discernible growth in specific domains, including interpersonal skills, stress management, adaptability, and general mood. Moreover, participants reported a notable enhancement in their interpersonal relationships and an elevated capacity to discern and regulate their emotions. The findings suggest that the intervention not only reinforced the emotional well-being of adolescents but also enhanced their ability to cope with stressful circumstances and adapt to changes. It is recommended that this type of program be incorporated into the educational domain to advance emotional and social growth, optimizing both academic performance and the general well-being of students.